Studi Literatur: Problematika Pembelajaran Matematika di Sekolah - Tiara Ayu An-nisa; Zahrotul Latifah; Ranggi Julian Syahputra; Rena Revita (Aksioma, 2026)
This study aims to describe various problems in mathematics learning in schools. The method used is Systematic Literature Review (SLR), with data collection carried out through the Publish or Perish and Google Scholar platforms. A total of 20 relevant journals from the period 2020 to 2025 were used as reference sources. The results of the study show that although mathematics has an important role in developing critical thinking skills and problem-solving skills, many students still find this subject difficult and confusing. Problems in mathematics learning are influenced by several main factors, namely: 1) student interest and motivation, 2) teaching methods applied, 3) support from the surrounding environment, and 4) the condition of available facilities and infrastructure. It is hoped that the results of this study can contribute to mathematics teachers in efforts to increase student interest and motivation in mathematics learning in schools.